In-Mine Treatment Of Acidic Drainage Using Anaerobic Bioreactors - Objective (The National Institute for Occupational Safety and Health (NIOSH), 1994)
To develop an in-mine water treatment system in which bacterial sulfate reduction and limestone dissolution continuously remove metals and acidity from contaminated drainage. Approach A section of mine tunnel was converted into a water treatment bioreactor by constructing cinder block dams and fang the area between them with a porous substrate mixture of limestone gravel and compost. Readily fermentable materials such as dairy whey, spent brewing yeast, or sugar were periodically added to the reactor. Mine drainage was impounded behind one of the dams and continuously percolates through the reactor substrate at a controlled rate. How It Works The reactor substrate soon becomes anaerobic after it is saturated with mine water. Under anaerobic conditions, sulfate-reducing bacteria consume the organic materials that are added to the reactor and generate hydrogen sulfide (HIS) and alkalinity. The H2S reacts with dissolved iron and heavy metals to form metal sulfide precipitates. The alkalinity raises the pH of the water and induces aluminum to hydrolyze and precipitate as aluminum hydroxide [Al(OH)3]. Additional alkalinity is generated by the continuous dissolution of the substrate limestone. Metal sulfide precipitates and Al(OH)3 are retained within the reactor, and the treated water is discharged. The underground location of the system allows year round operation.